Religious Tasamuh Processing Aplications In the Persfektive Of the Qur’an: Introduction, Methods, Tasamuh in Islam, Tasamuh in Aqidah Islamiyah, I'tiqad, Syari'ah, Vision The concept of the Qur’an builds tasamuh for humans - Z. Mutaqin; Jamaluddin; Ade Jamarudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Tasamuh is an attitude of respect for others to exercise their rights. We must not look down on ethnicity, religion, or other regional cultures, let alone contempt, hate, or antagonize them. Besides that, the meaning of tasamuh can also be interpreted as being patient in facing other people's beliefs, their opinions and their deeds even though they are contrary to beliefs and vanity in their eyes, and may not attack and criticize with reproaches that make that person sick and tormented by his feelings. Religious tolerance must be understood as a form of our acknowledgment of the existence of religions other than our own with all forms of systems and procedures for worship and giving freedom to carry out their respective religious beliefs. This research method is library research and is descriptive, analytic and comparative. Source of data used in this research comes from primary and secondary data. In collecting data using library books, journals, magazines, articles, interviews and documentation methods. The concept of tasamuh in the perspective of the Koran may not look down on ethnicity, religion, or other regional cultures, let alone contempt, hate, or be hostile towards them. In addition, the meaning of tasamuh can also be interpreted as being patient in facing other people's beliefs, their opinions and their deeds even though they are contrary to their beliefs and vanity in their eyes, and may not attack and criticize with reproaches that make the person sick and torment his feelings.